Elevating Subjective Well-Being Through Physical Exercises: An Intervention Study - Iwon, Katarzyna; Skibinska, Julia; Jasielska, Dorota; Kalwarczyk, Sonia (Frontiers in Psychology, 2021)
Background: Physical activity is associated with higher levels of subjective well-being. However, little research has been conducted in naturalistic conditions with a longitudinal design. In the current study, we aimed to examine whether regular activity initiation can impact happiness, life satisfaction and self-esteem four weeks later. Methods: The sample (N = 217, 169 women) was divided into three groups based on level of physical activity (active people, beginners and inactive people). The participants completed measures of happiness, satisfaction with life, self-esteem and a survey on physical activity. A total of 168 participants completed the same set of measures sent by email after four weeks. Results: The study showed a strong relationship between subjective well-being and physical activity. Active people showed higher levels of happiness and self-esteem compared to beginners and inactive people and a higher level of life satisfaction than inactive people. Furthermore, after four weeks of exercising, beginners revealed greater life satisfaction and happiness compared to the baseline. Conclusions: These findings confirm that regular physical activity leads to higher levels of well-being. It seems that even a short engagement in physical activity (four weeks) may contribute to an increase in subjective well-being.